Flip this house!: Updating and designing an online First Year Seminar module series. Issue 3 (1st October 2020) - Peuler, Mollie; Coltrain, Mark
Abstract: Appalachian State University's First Year Seminar Online Library Component is a set of information literacy modules designed to introduce students to university-level research. Originally deployed in 2015, this is a requirement for the University's First Year Seminar Program. It is composed of original and OER content, delivered through AppState's learning management system, and made the Libraries' programming more sustainable by replacing in-person instruction. This paper focuses on a redesign project that prioritized Universal Design for Learning, more authentic assessment, and creating awareness in a world of biased algorithms and fake news, engaging and preparing learners as they become global citizens.